Effect of six plant spacings on the four-year production of the yellow passion fruit in Porto Lucena, RS, Brazil - Manica, Ivo; Fioravanço, João C.; Barradas, Carlos I. N.; Kist, Hélio G. K; Kist, Henrique (Pesquisa Agropecuaria Brasileira, 1994)
This research was carried out in Porto Lucena, RS, Southern Brazil, aiming to evaluate the effect of six plant spacings on the production of the yellow passion fruit (Passiflora edulis f. flavicarpa Deg.) in four harvesting seasons. Plant spacings in the rows were 1.75; 2.00; 2.75; 3.50; 4.25 and 5.00 m, and between rows 2.50 m. The fruit weight and fruit number/plant was higher in the narrower plant spacing in the four harvestings and in the total cumulative production. For 1987, 1988, 1990 and total cumulative harvesting, fruit weight and fruit number/hectare were not influenced by plant spacing, while total fruit weight/hectare harvested in 1989 was higher in the 2.50 x 1.25 m plant spacing. Mean fruit weight was not influenced by any treatment.